If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x * 18x = 15x Reorder the terms for easier multiplication: 18 * 18x * x = 15x Multiply 18 * 18 324x * x = 15x Multiply x * x 324x2 = 15x Solving 324x2 = 15x Solving for variable 'x'. Reorder the terms: -15x + 324x2 = 15x + -15x Combine like terms: 15x + -15x = 0 -15x + 324x2 = 0 Factor out the Greatest Common Factor (GCF), '3x'. 3x(-5 + 108x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-5 + 108x)' equal to zero and attempt to solve: Simplifying -5 + 108x = 0 Solving -5 + 108x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 108x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 108x = 0 + 5 108x = 0 + 5 Combine like terms: 0 + 5 = 5 108x = 5 Divide each side by '108'. x = 0.0462962963 Simplifying x = 0.0462962963Solution
x = {0, 0.0462962963}
| 3(x+3)+2=9+2 | | 6/9=d/24 | | P/30+183=192 | | d/9=8 | | 7.50b-100=450 | | 10x-2x-3=4 | | K+174/13=26 | | 10/5=8/y | | 4x+2y+3y+7x= | | y-2(4)=0 | | 6x-36x=48-0.1 | | m=1/4 | | 12x=6x+9 | | 9x-2=9(x-1) | | 9x*9x=27x | | d/9=18 | | 6-(2p+3)+5(p-1)= | | 4d-11=2y+7 | | 3x+5=81 | | 42/12=14/n | | 5c=65 | | 15=10+1.5x | | 7-x=31-7x | | -3h+12-4h=7h-9-16 | | 15x=10+1.5x | | 12/36=p/100 | | a+5=13 | | 17h+31=558 | | x+6=20/2 | | 8p*8p-4p=0 | | -3+(-9)= | | Z/6-3=4 |